PENGARUH PERUBAHAN MEREK (REBRANDING) DAN KUALITAS PRODUK TERHADAP NIAT PEMBELIAN MELALUI SIKAP MEREK SEBAGAI VARIABEL INTERVENING (Studi Pada Konsumen Avoskin di Kota Semarang) - Riatri, Alya Yumna; Mahfudz, Mahfudz (Diponegoro Journal of Management, 2023)
ABSTRACT Technological growth in the world that is developing quite rapidly has caused the level of competition between companies to increase and requires companies to always innovate in maintaining their brands in the market. One of the efforts made by the company is to maintain its brand so that it remains relevant to the market is by change the brand logo. Avoskin is a brand in the beauty industry that creates beauty products that is currently focusing on facial skin care. Avoskin is always makes the best products from natural ingredients and devoid of the vision that everyone has the right to benefit from nature. On its 10th anniversary, in October 2022 to be precise, Avoskin changed its logo. This study aims to examine the effect of brand change (rebranding) and product quality on purchase intention with brand attitude as an intervening variable. The study was conducted on consumers who know the Avoskin brand, want to buy, and/ have used Avoskin products in the city of Semarang. This study used a purposive sampling technique with a total sample of 135 respondents. The method used in this study is the Structural Equation Model (SEM) using AMOS software 24.0. The results in this study indicate that the rebranding variable and product quality have a positive effect on the intervening variable brand attitude and the intervening variable has a positive and significant influence on purchase intention. Rebranding and product quality variables also have a positive and significant impact on purchase intention